The Relationship Between Middle School Students’ Critical Thinking Inclination and Reading Skills - DÖNER, Seyhan YILDIRIM; DEMİR, Sezgin (T.C. Milli Egitim Bakanligi, 2023)
Critical thinking inclination is the predisposition to the act of thinking based on inquisitive evaluation. Reading skill, which is a language skill for individuals to make sense of texts, also includes critical thinking. The purpose of this research is to reveal the relationship between middle school students’ critical thinking inclinations and their reading skills. The research was carried out in a quantitative, relational survey model. The sample of the research which was determined by the stratified purposeful method has been consisted of 1165 middle school students studying at state schools in the province of Tokat. Data collection tools are PISA Reading Skills Achievement Test and Critical Thinking Disposition Scale for Secondary School Students, which was developed by the researchers. T test, Anova, pearson correlation and regression were used to in the analysis of data. In the study, it was found that there was a positive relationship between the critical thinking inclinations of middle school students and their reading skills, and that their critical thinking inclinations predicted their reading skills by 3%. © (2023), (T.C. Milli Egitim Bakanligi). All Rights Reserved.
Ortaokul Öğrencilerinin Eleştirel Düşünme Eğilimleri İle Okuma Becerileri Arasındaki İlişki
Keywords: critical thinking inclination; PISA; reading skills; Turkish education